Effect of Plant Spacing and Harvesting Stage on Chemical Composition and In-Vitro Digestibility of Desho Grass (Pennisetum Glaucifolium L.) at Midland of Guji, Oromia Region - Teshale Beyene (International Journal of Scientific Multidisciplinary Research, 2024)
The experiment was conducted to evaluate appropriate combination harvesting stage and plant spacing on chemical compositions, digestibility and its rumen degradability potentials of Desho grass. Three-by-three randomized complete block design was used to set up the experiment. factorial arrangements in three replications. The experiment employs three harvesting stages (75, 105 and 135 days) and three plant spacing (10, 30 and 50 cm). Prior to planting 100 kg/ha-1 combinations of Nitrogen, phosphate and sulfur fertilizer were applied to all plots. The chemical composition such as CP, DM, TA, NDF, ADF, ADL, cellulose and CPY and DMY yield parameters differed considerably (p<0.01). Hemi cellulose concentration, however, was not substantially (p>0.05) impacted. With the 30*105 combination, a higher dry matter yield (31.87 t/ha) was achieved. The treatment combination of 30*105 had the greatest CP content (12.37%). Treatment combinations have an impact on the properties of crude protein and dry matter in-sacco degradability. Thus, it is possible to conclude that, the treatment combination 30 cm*105 days has resulted in optimum yield and nutritive values of Desho grass under the current experiment around Adola. However, there is a need for further studies on different combinations of harvesting stage and plant spacing over years and locations to arrive at dependable conclusions